Degree of mass media exposure in English language and linguistic errors in oral English orientation among Grade VII students of Digos City National High School - Asan, Ruben; Flores, Galileo Jr.; Miralles, Jodel; Emnace, Vangie (UM Digos Research Journal, 2016)
Media is one of the main pursuant to direct exposure in learning a second language, from television shows and other interactive multi-media preferences and simple instruction manuals; we see that most of these consist an input of secondary language we perceive and we are exposed to in daily basis. Because media contributes most exposure, we come to know the underlying questions to how much or what degree or impact does secondary language has oriented us through the Media that are present; also knowing what degree of linguistic error it establishes through the actual application of secondary language. A variable was met to understand the extent of exposure to various media on a certain controlled level. The study underlines the hypothetical fact why media exposure is a factor for the chosen variable in determining the degree of linguistic errors. It is studied how Grade VII students responded and what various errors are accumulated that is the basis on defining the study. Considering that the study’s controlled variable has an existing English input from their previous academic background, the study implies the level of common errors that may serve as the basis on secondary levels.